The morbidity of laparoscopic radical cystectomy: analysis of postoperative complications in a multicenter cohort by the European Association of Urology (EAU)-Section of Uro-Technology - Albisinni, Simone; Rassweiler, Jens; Teber, Dogu (World journal of urology, 2016)
Purpose To analyze postoperative complications after laparoscopic radical cystectomy (LRC) and evaluate its risk factors in a large prospective cohort built by the ESUT across European centers involved in minimally invasive urology in the last decade. Methods Patients were prospectively enrolled, and data were retrospectively analyzed. Only oncologic cases were included. There were no formal contraindications for LRC: Also patients with locally advanced tumors (pT4a), serious comorbidities, and previous major abdominal surgery were enrolled. All procedures were performed via a standard laparoscopic approach, with no robotic assistance. Early and late postoperative complications were graded according to the modified Clavien-Dindo classification. Multivariate logistic regression was performed to explore possible risk factors for developing complications. Results A total of 548 patients were available for final analysis, of which 258 (47 %) experienced early complications during the first 90 days after LRC. Infectious, gastrointestinal, and genitourinary were, respectively, the most frequent systems involved. Postoperative ileus occurred in 51/548 (9.3 %) patients. A total of 65/548 (12 %) patients underwent surgical re-operation, and 10/548 (2 %) patients died in the early postoperative period. Increased BMI (p = 0.024), blood loss (p = 0.021), and neoadjuvant treatment (p = 0.016) were significantly associated with a greater overall risk of experiencing complications on multivariate logistic regression. Long-term complications were documented in 64/548 (12 %), and involved mainly stenosis of the uretero-ileal anastomosis or incisional hernias. Conclusions In this multicenter, prospective, large database, LRC appears to be a safe but morbid procedure. Standardized complication reporting should be encouraged to evaluate objectively a surgical procedure and permit comparison across studies.